Existential analysis of mothers in the care of their children with Sickle Cell Disease - Camila Messias Ramos; Zuleyce Maria Lessa Pacheco; Iêda Maria Ávila Vargas; Paulo Afonso Araújo (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to unveil the experience of mothers of children who had a cerebrovascular accident due to sickle cell disease. Methods: qualitative, phenomenological research based on Martin Heidegger's philosophical framework. Ten mothers participated in the Association of People with Sickle Cell Disease of Minas Gerais. For the interpretative analysis of the reports, we performed the vague and medium understanding followed by hermeneutics. Results: the study revealed that, for the mother, the experience means remembering the diagnosis of the disease that had a significant impact. These women are in the center of care, and the consequences of stroke cause suffering. In this wandering, they seek to educate their children as close as possible to normal. Final Considerations: the study pointed out that we should look at these mothers seeking to see the multiple facets of their existence to the challenge of caring for the existential complexity of the human being.